ANALISA PENGARUH GIRO DAN DEPOSITO SEBELUM DAN SETELAH DIKELUARKANNYA PAKTO 1988 DI INDONESIA - Muhammad Umar Nuh; Suhel Suhel; Jatmiko Jatmiko (Jurnal Ekonomi Pembangunan, 2004)
This research is intended to analyze the effect between demand deposits and time deposits against banking credit dispensasion in Indonesia, on the period of pre-annouced and post announced the October Deregulation Package 1988. The out come of this research is supposed to be the transformation that explain the demand deposits and time deposits effect on banking credit distribution even before or after. The October Deregulation Package 1988. The data that is used in this research is secondary data which is from various sources, some of them are statistics center Burew, any lioterature, magazines, and books. The analisist on this research is using the double linear regretion model. From the analisist result, Known R2 for the period of pre-announced The October Deregulation Pankage is equal to 0,972 according to the demand deposits effect against on banking credit and for the time deposits effect  against  banking credit is equal to 0,994. On the other hand, for the period of post announced The October Deregulation Package 1988, R2 is equal to 0,631. The statistic test (t-test) result for the time deposits effect against banking credit dispensation in the period of post announced  The  October Deregulation  Package  1988 is significant. On the same case, in the period of post-announced The October Deregulation  Package  198, the result is not significant. It caused by proportion of demand deposits using against banking credit dispensation is on low level.   Keywords: Demand and Time Deposits, Bankring Credits